2019
DOI: 10.34208/jba.v20i2.412
|View full text |Cite
|
Sign up to set email alerts
|

Profitabilitas, Leverage, Komposisi Dewan Komisaris, Komite Audit, Dan Kompensasi Rugi Fiskal Terhadap Penghindaran Pajak Pada Perusahaan Perbankan

Abstract: Tax avoidance has been a main concern of almost in the world. It is mostly done by tax payer due to its legality. This study aims to analyze factors affecting tax avoidance (i.e, profitability, leverage, independent bord, audit committee, and fiscal loss compensation) with firm size as a control variable. Implementing purposive sampling approach, this study ended-up with 30 companies for 2011-2015 period (i.e., 150 observations). By using OLS regression, the findings shows that profitability influences positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0
34

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 10 publications
(21 reference statements)
4
5
0
34
Order By: Relevance
“…This research is in line with the results obtained by Putriningsih et al (2018), Angelia and Dwimulyani (2019), Putra and Jati (2018), Oktamawati (2017), Prapitasari and Safrida (2019), and Yulyanah and Kusumastuti (2019) who found that profitability has a positive effect on tax avoidance. Profitability is one of the benchmarks for a company in its ability to earn profits for the company's going concern.…”
Section: Effect Of Profitability On Tax Avoidancesupporting
confidence: 92%
“…This research is in line with the results obtained by Putriningsih et al (2018), Angelia and Dwimulyani (2019), Putra and Jati (2018), Oktamawati (2017), Prapitasari and Safrida (2019), and Yulyanah and Kusumastuti (2019) who found that profitability has a positive effect on tax avoidance. Profitability is one of the benchmarks for a company in its ability to earn profits for the company's going concern.…”
Section: Effect Of Profitability On Tax Avoidancesupporting
confidence: 92%
“…Menurut Dewi Putriningsih et al, (2018) utang yang menyebabkan munculnya beban bunga dapat menjadi pengurang laba kena pajak, sedangkan deviden yang berasal dari laba ditahan tidak dapat digunakan sebagai pengurang laba. Beban bunga yang dapat digunakan sebagai pengurang laba kena pajak adalah beban bunga yang muncul akibat adanya pinjaman kepada pihak ketiga atau kreditur yang tidak memiliki hubungan denga perusahaan, sebagaimana diatur dalam UU No.36 tahun 2008 pasal 6 ayat 1a dan pasal 18.…”
Section: Leverage Berpengaruh Terhadap Tax Avoidanceunclassified
“…Dan (Diantari & Ulupui, 2016) Hasil variabel kontrol berupa leverage adalah 0.0169 dan nilai regresi koefisien -0.0770 yang artinya adalah memiliki pengaruh yang signifikan negatif terhadap penghindaran pajak. Hasil yang didapatkan juga didukung oleh Putriningsih et al, (2019) dan Richardson dan Lanis (2007) sehingga membuktikan bahwa semakin tinggi beban utang suatu perusahaan, maka semakin kecil pula jumlah pajak yang harus dipenuhi oleh perusahaan tersebut. Variabel kontrol ROA menunjukkan hasil 0.0891 dengan nilai koefisien -0.0747 yang berarti ROA memiliki hubungan negatif tetapi tidak signifikan terhadap penghindaran pajak.…”
Section: Pembahasanunclassified